Results from the Canadian Nosocomial Infection Surveillance Program for detection of carbapenemase-producing Acinetobacter spp. in Canadian hospitals, 2010–16. (12th October 2018) - Boyd, David A; Mataseje, Laura F; Pelude, Linda; Mitchell, Robyn; Bryce, Elizabeth; Roscoe, Diane; Embree, Joanne; Katz, Kevin; Kibsey, Pamela; Lavallee, Christian; Simor, Andrew E; Taylor, Geoffrey; et al.
Abstract: Objectives: Globally there is an increased prevalence of carbapenem-resistant Acinetobacter spp. (CRAs) and carbapenemase-producing Acinetobacter spp. (CPAs) in the hospital setting. This increase prompted the Canadian Nosocomial Infection Surveillance Program (CNISP) to conduct surveillance of CRA colonizations and infections identified from patients in CNISP-participating hospitals between 2010 and 2016. Methods: Participating acute care facilities across Canada submitted CRAs from 1 January 2010 to 31 December 2016. Patient data were collected from medical records using a standardized questionnaire. WGS was conducted on all CRAs and data underwent single nucleotide variant analysis, resistance gene detection and MLST. Results: The 7 year incidence rate of CRA was 0.02 per 10 000 patient days and 0.015 per 1000 admissions, with no significant increase observed over the surveillance period ( P  >   0.73). Ninety-four CRA isolates were collected from 58 hospitals, of which 93 (98.9%) were CPA. Carbapenemase OXA-235 group (48.4%) was the most common due to two separate clusters, followed by the OXA-23 group (41.9%). Patients with a travel history were associated with 38.8% of CRA cases. The all-cause 30 day mortality rate for infected cases was 24.4 per 100 CRA cases. Colistin was the most active antimicrobial agent (95.8% susceptibility). Conclusions: CRA remains uncommon in Canadian hospitals and the incidence did not increase from 2010 to 2016. Almost half of the cases were from two clusters harbouring OXA-235-group enzymes. Previous medical treatment during travel outside of Canada was common.